Insurance and Redistribution with Simple Tax Instruments - Dominik Sachs; Sebastian Findeisen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study optimal nonlinear taxation of labor income and linear taxation of capital income in a life-cycle framework with private information and idiosyncratic risk. We focus on simple history-independent tax instruments. We first analyze the welfare losses from this simplification as compared to optimal history-dependent policies. We find very small losses from restricting the complexity of savings wedges. Eliminating history dependence of labor wedges leads to larger welfare losses: moving from history dependence to age dependence yields approximately the same welfare losses as moving from age dependence to age independence and from nonlinear to linear income taxation. For optimal history- independent taxes, we provide a novel decomposition into a redistribution and an insurance component and a generalization of the top tax formula to dynamic environments. Capital taxation is desirable and yields sizable welfare gains, especially if labor income taxes are set below their optimal level.
Keywords: H21; H20; H23; 330